Estimation of cost savings between 2011 and 2014 attributed to infliximab biosimilar in the South Korean healthcare market: real‐world evidence using a nationwide database. (17th April 2018) - Kim, Jiyoun; Ha, Dongmun; Song, Inmyung; Park, Haesun; Lee, Sang‐Won; Lee, Eui‐Kyung; Shin, Ju‐Young
Abstract: Aim: The introduction of biosimilars is expected to reduce the cost of biologic drugs, but the actual cost savings have not yet been quantified in Korea. The aim of this study was to estimate the annual cost savings attributed to the introduction of infliximab biosimilar. Methods: We conducted a retrospective analysis using data from the Health Insurance Review and Assessment Service‐National Patients Sample (HIRA‐NPS) between 2011 and 2014. The study subjects were patients who were treated with infliximab, adalimumab or etanercept. We compared the drug costs before and after the introduction of infliximab biosimilar in December 2012 (2011–2012 and 2013–2014) to estimate the annual drug cost savings attributed to this and the number of patients who could additionally benefit from the biosimilar in 2013 and 2014. Results: A total of 10 986 prescriptions were identified: 2620 for infliximab. The cost savings were estimated at 262 270 for 133 patients in 2013 and 395 220 for 174 patients in 2014. Among the patients who underwent a 1‐year maintenance course of infliximab therapy, the annual expenditure on infliximab was lower in 2014 than in 2011. If the cost savings were used to treat additional patients, 13.3%–38.6% more patients per year could be treated by indication. Conclusion: The introduction of infliximab biosimilar reduced direct medical costs for both patients and the payer, which could then be used to increase patient access to biologic medicines. The entry of infliximab biosimilar could result in further reductions in healthcare costs.